How to communicate in business a handbook for engineers - Silk, D. J. (David J.) (Institution of Electrical Engineers, 1995)
This book aims to help engineers to communicate effectively with nonengineers, in the business context. It will also be useful to people from other technical or numerate backgrounds. It will help you to consider the various methods of communication used in business, and consciously develop your own skills. The approach is practical, although built upon some simple ideas of what we mean by communication, and its role in the business enterprise. Major chapters deal with spoken communication, written communication, business presentations and business meetings. They cover the main communication skills that an engineer is likely to need, both in a professional capacity and in a management or administrative capacity. Cross-cultural and international aspects are considered. A chapter on the use of information technology deals with IT as a personal aid, and also internal and external networks which operate in the text, data, voice and image modes. Each requires good technique to release its full benefit. All chapters include practical advice and questions to help your self assessment and development. The final chapter suggests how you can construct a personal action plan, and help in the development of your colleagues.